EXPLORING STUDENTS’ WILLINGNESS TO COMMUNICATE USING ENGLISH IN AN ISLAMIC BOARDING SCHOOL - Kusumawati, Anita (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Speaking English has been as a major of focus on language learning, as being able to communicate using the language is being the learning target to be achieved by the learners. However, in performing speaking ability, many aspects appear to be taken into account such as the language knowledge itself as well phycological aspects of the students which involve students’ individual differences. Willingness to communicate as one of individual differences factor has been prominently believed might affect students’ language speaking performance. The context of this study is in an Islamic boarding school located in Tangerang Selatan. The aim of this study is to explore students’ willingness and unwillingness to communicate in English speaking activities and investigate the factors affected their willingness to communicate using English in the context. The methodology in conducting this study is qualitative method and the data will be obtained from questionnaire which is designed to answer the research question in this study. The participants are fifty three secondary students in the boarding. The results indicate that majority of the students have interest to communicate using English. The outcomes emerged from findings in this study show some factors contribute to students’ willingness to communicate can be classified into intrinsic and extrinsic factors, and aspects that might prevent students to speak English involve linguistic and non-linguistic elements.